From e-service quality to behavioral intention to use e-fitness services post COVID-19 lockdown: when a crisis changes the social mindset - Teva Villén, María Rosario; García Fernández, Jerónimo; Bohorquez, María Rocío; Lara Bocanegra, Alejandro; Grimaldi, Moisés (Heliyon, 2025)
Lockdowns resulting from the COVID-19 pandemic forced fitness centers to quickly adapt their entire offering to an online format. The subsequent health situation facilitated the maintenance of the online offer and has been a paradigm shift for sports centers. Success in the nowadays situ- ation requires a proper understanding of what factors influence e-service quality and how these factors behave in relation to consumer satisfaction, attitudes toward online fitness services, and behavioral intentions. This research was conducted in April 2020, with 745 participants (492 women, 253 men) completing the Carlson and O’Cass e-service quality evaluation battery. The results showed that e-service quality during the lockdowns predicted attitudes toward the digital platforms and behavioral intentions, and e-service quality predicted attitudes and behavioral intentions. However, attitudes did not predict behavioral intentions; the possible influence of subjective norms and low perceived control in this particular situation is discussed. When offering services on digital platforms, fitness service managers must take into account the importance of the quality of the e-fitness service, but also the social context in which it is offered. Psychosocial functioning in times of crisis influences users’ perceived control and their future intention to use online services.
Keywords: e-service quality; e-fitness service; consumer satisfaction; attitudes; behavioral intentions; digital platforms